Experimental study on foaming characteristics and microstructure of self-expanding polymer grouting material under low-temperature conditions - Songtao Li; Baolin Wang; Yanlong Gao (PLoS ONE, 2025)
Polymer grouting materials, due to their self expansion properties, have been widely used in repair engineering involving hydraulic structures and have become a new type of building material. The foaming characteristics of polymer grouting materials under low-temperature conditions directly influence their repair effectiveness in cold areas. In this study, a grouting test of the free expansion of the polymer grouting material in the vertical direction and a mold grouting test with all four sides constrained were performed under different low-temperature conditions. The structure and morphology of foam cells under different low-temperature conditions were examined via scanning electron microscopy. The test results indicated that as the temperature decreased, the volume of the foam gradually exhibited a cold shrinkage effect, and the surface temperature gradually decreased. For every 1°C decrease in temperature, the foaming volume decreases by an average of 40 cm3, and the surface temperature decreases by an average of 1.7°C. According to the foaming rate, the foaming process was divided into three stages: fast, slow, and stable foaming. Additionally, the internal temperature stress generated during the foaming process was a key factor that caused the foam to bulge outward. Under the condition where all four sides were constrained, the density of the foam formed gradually decreased as the temperature decreased. The foam cell was spherical. As the temperature decreased, the cell morphology became blurred, and the number of incomplete cell structures between the gaps increased. The research results will provide a reference for the polymer repair projects of hydraulic structures in cold regions.